Impact of Achieving Optimal Treatment Targets and Minimal Disease Activity on Health-Related Quality of Life and Satisfaction in Patients with Atopic Dermatitis - Jonathan I. Silverberg; Melinda Gooderham; Andreas Wollenberg; Andrew E. Pink; Diego Ruiz Dasilva; Shawn G. Kwatra; Yousef Binamer; Norito Katoh; Valeria Aoki; Alvaro Moreira; Ayman Grada; Chao Li; et al. (Dermatology and Therapy)
Abstract Introduction Guidance from the Aiming Higher in Eczema/Atopic Dermatitis initiative identified moderate and optimal treatment targets for clinician-reported outcomes (ClinROs) and patient-reported outcomes (PROs) and defined minimal disease activity (MDA) as simultaneously meeting optimal targets in ClinRO and PRO. This post hoc analysis investigates the impact of achieving individual optimal targets or MDA on patient health-related quality of life (HRQoL) outcomes in patients with atopic dermatitis. Methods Patients from phase 3 Measure Up 1 (NCT03569293), Measure Up 2 (NCT03607422), and AD UP (NCT03568318) were randomized 1:1:1 to receive daily oral upadacitinib at either 15 mg or 30 mg, or placebo for the first 16 weeks. Patients were pooled for this analysis regardless of intervention and stratified into three mutually exclusive response groups meeting optimal, moderate, or neither treatment target for each ClinRO or PRO, and the achievement of MDA at week 16. Impact on the patient’s HRQoL was measured across eight outcomes: itch, skin symptoms, quality of life, sleep, daily activities, emotional state, work productivity, and treatment satisfaction. Results Patients who achieved optimal treatment targets, compared with those achieving moderate or neither treatment target, reported greater improvement in patient HRQoL outcomes (1.1–20.2-fold for optimal versus moderate, 1.3 to > 50-fold for optimal versus neither target, and 1.2–16.3-fold for moderate versus neither target groups). In addition, patients who achieved MDA, versus those achieving optimal ClinRO or PRO alone, were more likely to report improved patient HRQoL outcomes. Conclusions These results highlight the value of reaching optimal treatment targets and MDA in disease management of atopic dermatitis.